Social alienation and influencing factors among caregivers of stroke patients in China: a cross-sectional study - Xu, Lang; Liu, Shanshan; Luo, Mao; Li, Min; Wang, Cong (Frontiers in Psychiatry, 2025)
IntroductionAs the primary bearers of post-stroke rehabilitation and long-term care, caregivers of stroke patients in China face a profound sense of social alienation that has not yet been fully recognized due to issues such as role-related limitations. Especially in the context of China’s family caregiving model and evolving social support system, this sense of alienation not only undermines the physical and mental health of caregivers, but also ultimately affects the quality of ongoing rehabilitation support. This is undoubtedly detrimental to both care providers and recipients. Therefore, the aim of this study was to investigate the level of social alienation and its influencing factors among Chinese stroke caregivers.MethodsParticipants for this study were selected from caregivers of stroke patients who visited the neurology department of a comprehensive hospital in Kunming between February and August 2023. A total of 222 stroke caregivers were assessed using the General Alienation Scale, the Zarit Caregiver Burden Interview, the Social Support Rating Scale, and the University of California at Los Angeles-Loneliness Scale.ResultsThe mean social alienation scores for the stroke caregivers included in this study were 40.45 ± 4.76 (range:24-51).Multivariate linear regression analysis revealed that the marital status of caregivers, whether they live with the patient, their knowledge of the disease, social support, caregiving burden, and loneliness are significant factors influencing social alienation in stroke caregivers (all p < 0.05).ConclusionsCaregivers of stroke patients experience high levels of social alienation. It is crucial to address the social alienation of these caregivers, particularly those who live with the patient, are divorced or widowed, have limited knowledge of the disease, bear a heavy caregiving burden, have low levels of social support, and experience high levels of loneliness. Targeted and individualized interventions should be developed to reduce their social alienation.